Cerebral aneurysm treatment: modern neurovascular techniques. Issue 3 (17th August 2016) - Jiang, Bowen; Paff, Michelle; Colby, Geoffrey P; Coon, Alexander L; Lin, Li-Mei
Abstract : Endovascular treatment of cerebral aneurysm continues to evolve with the development of new technologies. This review provides an overview of the recent major innovations in the neurointerventional space in recent years.